INCOME ANALYSIS AND DEVELOPMENT STRATEGY OF BROWN SUGAR FROM PALM SAP (Elaeis guineensis Jacq) - Iqlima Syafira; Rahmanta; Iskandarini (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Serdang Bedagai, is one of the production centers for processing palm sap into brown sugar, this business requires a well-planned concept that produces alternative strategies. This research aims to analyze the income and development strategy of palm oil palm nira brown sugar business in Serdang Bedagai. This research uses quantitative analysis methods to determine the level of income and business feasibility analysis of brown sugar from palm sap and descriptive analysis to explain SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) to see the internal environment, namely strengths and weaknesses and the external environment, namely opportunities and threats of brown sugar from palm sap business. The results showed an income level of IDR. 18,039,877 and an R/C feasibility analysis of IDR. 1.14 that the brown sugar from palm sap business is feasible. The business development strategy of palm sap brown sugar is in quadrant I (1,22 and 1,92). Namely by increasing the production capacity of brown sugar from palm sap, expanding new customer segments, improving the quality of palm nira brown sugar processing. This is very possible to see from the availability of abundant raw materials and high market demand.